Representação, acesso, uso e reuso da imagem digital - Simionato, Ana Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In search of real or memory, imaging techniques along with the technology advance, with unimaginable numbers of information stored and disseminated in digital media. There are several devices on the market that when used, store and reproduce their expressions with no concern for the treatment of information. However, all these expressions imagery require efficient recovery, otherwise it will live in a digital disorder. In this sense, the objective of this study is to determine within a context intersemiotic, the construction of representations of digital images, based on the instruments in the field of bibliography, Description of Treatment Information (TDI), by presenting a conceptual model for digital images. The methodology consists of a descriptive and exploratory analysis of available literature on the theme, which allows the construction of a theoretical knowledge of the instruments that guide the construction of representations in the field of Information Science, the description is constructed from an observation qualitative systematic material by means of parameters describing imagery. Retrieval Systems Based on Image Content (CBIR) explained the need for the introduction of new expressions, such as using features of color, shapes and textures. However, only the properties imagery not solve the problem for the recovery of images, for construction of the description of the object informational must ensure its uniqueness, so that it can be inserted in different contexts maintaining the integrity of data. In this context, the use of tools for describing information resources is required. The results present the Functional Requirements for Digital Imagery Data - RFDID, with the view that the guarantee of data persistence and instancing feature with consistency and integrity are essential requirements for the representation of a digital image

Em busca do real ou da lembrança, as técnicas da imagem junto com a tecnologia avançam, com números inimagináveis de informações armazenadas e disseminadas no meio digital. Há diversos dispositivos no mercado, que quando utilizados, armazenam e reproduzem suas expressões sem uma adequada preocupação com o tratamento informacional. Contudo, todas essas expressões imagéticas necessitam de uma recuperação eficiente, caso contrário, se viverá em uma desordem digital. Neste sentido, o objetivo desse trabalho é determinar dentro de um contexto intersemiótico, a construção de representações das imagens digitais, tendo como base os instrumentos no domínio bibliográfico, do Tratamento Descritivo da Informação, com a apresentação de um modelo conceitual para imagens digitais. A metodologia consiste em uma análise exploratória e descritiva da literatura disponível sobre o tema proposto, que permite a construção de um conhecimento teórico sobre os instrumentos que orientam a construção de representações na área de Ciência da Informação, a descrição é construída a partir de uma observação sistemática qualitativa dos materiais, por meio dos parâmetros de descrição imagética. Os sistemas de Recuperação da Imagem Baseado em Conteúdo (CBIR) explicitaram a necessidade da introdução de novas expressões, como a utilização de feições de cor, formas e texturas. Contudo, somente as propriedades imagéticas não solucionam o problema para o acesso as imagens, pois construção da descrição do objeto informacional deve garantir sua unicidade, de modo que, possa ser inserida em diferentes contextos mantendo a integralidade dos dados. Nesse contexto, a utilização dos instrumentos para descrição...
Keywords: Imagens digitais; Ciência da informação; Catalogação; Metadados; Digital images; Information science; Cataloging; Metadata